Determinan Status Upah Tenaga Kerja Terdidik di Indonesia - Salsabila, Sitta Auliya; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
During the last seven years, unemployment in Indonesia has been dominated by the educated workforce. The limited number of educated workers in the labor market, there has been speculation about a decent wage for educated workers. Unemployment is also related to the length of time looking for work which depends on the wages offered and the expected minimum wage. Therefore, it’s necessary to study the wages received by educated workers so that wage conditions for educated workers in Indonesia can be identified. This study also aims to analyze the variables that influence trends in the wage status of educated workers. The analytical method used is descriptive analysis in diagrams and inferential analysis with binary logistic regression. The results showed that educated workers with college education levels, male, aged 25 years and over, worked at least 35 hours a week, worked for at least 6 years, and attended job training have a greater tendency to get wages above the regional minimum wage.